2021
DOI: 10.3389/fneur.2021.752698
|View full text |Cite
|
Sign up to set email alerts
|

Direct Endovascular Thrombectomy or With Prior Intravenous Thrombolysis for Acute Ischemic Stroke: A Meta-Analysis

Abstract: Background and purpose: It is unclear whether endovascular thrombectomy alone compared with intravenous thrombolysis combination with endovascular thrombectomy can achieve similar neurological outcomes in patients with acute large vessel occlusion stroke. We aimed to perform a systematic review and meta-analysis of randomized controlled trials to compare endovascular thrombectomy alone or intravenous thrombolysis plus endovascular thrombectomy in this population.Methods: We systematically searched PubMed, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Compared with two recent published systematic reviews addressing EVT alone versus EVT with intravenous thrombolysis in acute ischaemic stroke from large vessel occlusion,34 35 our review had the following distinctions. First, we used the GRADE approach to evaluate the certainty of evidence, which formally acknowledges imprecision in effect estimates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with two recent published systematic reviews addressing EVT alone versus EVT with intravenous thrombolysis in acute ischaemic stroke from large vessel occlusion,34 35 our review had the following distinctions. First, we used the GRADE approach to evaluate the certainty of evidence, which formally acknowledges imprecision in effect estimates.…”
Section: Resultsmentioning
confidence: 99%
“…In the systematic review of four trials, surrogate endpoints (successful reperfusion and any intracranial haemorrhage) showed significant improvement, the first favouring EVT plus alteplase and the second favouring EVT alone, and the authors did not address this issue 34. In the systematic review of three trials, there were no significant differences in successful reperfusion 35. Surrogate outcomes are less important when we have evidence to directly inform patient-important outcomes 36.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRISMA flow diagram of search strategy and the process of screening and study selection are shown in figure 1. Twenty-five relevant studies were finally included in qualitative synthesis 15–20 24–42…”
Section: Resultsmentioning
confidence: 99%
“…Several RCTs (eg, DIRECT-MT, DEVT, SKIP, MR CLEAN-NO IV, SWIFT DIRECT, and DIRECT-SAFE) and observational studies have been performed, greatly updating the clinical evidence available to clinicians 9–14. Subsequently, meta-analyses have attempted to further clarify this issue 15–20. However, these attempts and their source data differ in their methodologies and data reporting systems, limiting the ability to accurately assimilate data from different studies.…”
Section: Introductionmentioning
confidence: 99%